Real time data streaming from smart phones - Rowlands, D.; James, D. (Procedia Engineering, 2011)
There are many aspects of the athlete's performance that can and need to be measured to improve performance or to fine-tune skills. This can be done visually by a coach or by using sensors attached to the athlete. This paper discusses the common sensor data capture methods and the main requirements for a data capturing system with special attention paid to the requirements for a real time data capturing system. An implementation of a real time data capture system consisting of an iPhone and a laptop is presented. The system was tested on a runner performing a slow jog. The acceleration signatures for the running was streamed from the iPhone to the laptop and displayed in real time thus validating the system.